Enactive cinema paves way for understanding complex real-time social interaction in neuroimaging experiments - Tikka, Pia; Väljamäe, Aleksander; de Borst, Aline; Pugliese, Roberto; Ravaja, Niklas; Kaipainen, Mauri; Takala, Tapio (Frontiers in Human Neuroscience, 2012)
We outline general theoretical and practical implications of what we promote as enactive cinema for the neuroscientific study of online socio-emotional interaction. In a real-time functional magnetic resonance imaging (rt-fMRI) setting, participants are immersed in cinematic experiences that simulate social situations. While viewing, their physiological reactions - including brain responses - are tracked, representing implicit and unconscious experiences of the on-going social situations. These reactions, in turn, are analysed in real-time and fed back to modify the cinematic sequences they are viewing while being scanned. Due to the engaging cinematic content, the proposed setting focuses on living-by in terms of shared psycho-physiological epiphenomena of experience rather than active coping in terms of goal-oriented motor actions. It constitutes a means to parametrically modify stimuli that depict social situations and their broader environmental contexts. As an alternative to studying the variation of brain responses as a function of a priori fixed stimuli, this method can be applied to survey the range of stimuli that evoke similar responses across participants at particular brain regions of interest.